Producto Turístico y Marketing Turístico en la Comunidad Galte Laime, Parroquia Palmira, Provincia Chimborazo. - Muñoz Vite, Dayana Cristina (2023)
The current research work achieves the objective of relating the product and community-based tourism marketing. Additionally, it establishes the connection between the way in which tourism services are seen and the community services themselves, between the infrastructure for tourism and the method of pricing, and between the estimation of tourism resources and local tourism promotion. Cross-sectional research, non-experimental design, with quantitative, qualitative, case study types of research is declared. The scientific methods declared, the analysis and synthesis of information sources, expert method, method of analysis and synthesis, mathematical statistical method, empirical method. The results show that there is a relationship between the variables of the tourism product and the variable of tourism marketing, demonstrating the need for tourism actors to re-evaluate the approaches of tourism marketing in relation to the tourism product on offer. There is a relationship between infrastructure and pricing strategy based on the impact of infrastructure state on customer perception of price and lack of differentiation from competing communities' offerings or understanding of infrastructure's scope. There is a connection between community-wide tourism promotion efforts and tourist resources when it comes to making attractions visible, with the Internet serving as the ideal promotional channel. The intention is to improve the tourism marketing strategy's focus on each offered travel product by disseminating this tool to the other tourist communities in the province of Chimborazo.